Effects of uv irradiation and storage on the performance of inverted red quantum-dot light-emitting diodes - Luo Y.; Wang J.; Wang P.; Mai C.; Wang J.; Yap B.K.; Peng J. (MDPI AG, 2023)
We report the effects of ultraviolet (UV) irradiation and storage on the performance of ZnO-based inverted quantum-dot light-emitting diodes (QLEDs). The effects of UV irradiation on the electrical properties of ZnO nanoparticles (NPs) were investigated. We demonstrate that the charge balance was enhanced by improving the electron injection. The maximum external quantum efficiency (EQE) and power efficiency (PE) of QLEDs were increased by 26% and 143% after UV irradiation for 15 min. In addition, we investigated the storage stabilities of the inverted QLEDs. During the storage period, the electron current from ZnO gradually decreased, causing a reduction in the device current. However, the QLEDs demonstrated improvements in maximum EQE by 20.7% after two days of storage. Our analysis indicates that the suppression of exciton quenching at the interface of ZnO and quantum dots (QDs) during the storage period could result in the enhancement of EQE. This study provides a comprehension of the generally neglected factors, which could be conducive to the realization of high-efficiency and highly storage-stable practical applications. 2021 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).